Applying Lessons Learned from Developing Exon Skipping for Duchenne to Developing Individualized Exon Skipping Therapy for Patients with Neurodegenerative Diseases - Aartsma-Rus, Annemieke (Synlett, 2023)
Antisense oligonucleotides (ASOs) are short, modified pieces of DNA that are chemically modified. They can be used to induce exon skipping and treat Duchenne muscular dystrophy (DMD) patients by interfering with the splicing process so mutated dystrophin transcripts become readable allowing production of partially functional dystrophin proteins, rather than nonfunctional dystrophins. After over 2 decades of research, 4 ASOs are FDA approved for DMD, but clinical effects are suboptimal due to limited delivery to skeletal muscle. At the same time, ASOs for brain diseases result in much more functional impact, because local delivery allows higher exposure to the target tissue at a low dose and infrequent treatment regimen. This has opened the way to develop ASOs in an individualized setting, as was exemplified by the development of Milasen to treat a patient with CLN7 Batten disease.In this perspective paper I will share my personal journey as one of the pioneers of ASO-mediated exon skipping development for DMD, currently applying expertise gained and lessons learned along the way to develop exon skipping ASOs for eligible patients with genetic brain diseases in a national and international setting.1 Duchenne and Antisense-Mediated Exon Skipping2 Opportunities for Treating Central Nervous System Diseases and Developing Individualized ASOs for Central Nervous System Diseases3 Collaborative Spirit to Develop Individualized Treatments Globally4 Global Implementation5 Concluding Remarks
Keywords: antisense oligonucleotide; exon skipping; N-of-1 treatment; rare disease; therapy